Frogs : the animal answer guide - Dorcas, Michael E., 1963- (Animal Answer Guides: Q & A for the Curious Naturalist., 2011)
"Frogs are amazingly diverse--ranging from the massive Goliath frog, which weighs several pounds, to the discovered gold frog, which measures a mere three-eighths of an inch when fully grown--and have inhabited the earth for more than 200 million years. Today, however, these amphibians face more challenges than any other vertebrate group. In this fun and informative book, herpetologists Mike Dorcas and Whit Gibbons answer common and not-so-common questions people may have about these fascinating animals."--Back cover.